2019
DOI: 10.4103/abr.abr_126_18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Resistin, Endothelin-1, and Flow-Mediated Dilation in Patient with and without Metabolic Syndrome

Abstract: Background:Resistin is peptides that signal the functional status of adipose tissue to the brain and other target organs. It causes insulin resistance and affects the vascular endothelial dysfunction. However, the function and relation between resistin in endothelin-1 (ET-1), which leads to the endothelial dysfunction in humans are enigmatic.Materials and Methods:In a cross-sectional study of 76 participants (38 metabolic syndrome patients and 38 healthy participants), biochemical and clinical parameters, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In line with this, several studies reported a positive association between HDL-C levels and FMD [27][28][29][30][31]. However, several other studies showed either no association or even found a negative association between HDL-C and FMD [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 62%
“…In line with this, several studies reported a positive association between HDL-C levels and FMD [27][28][29][30][31]. However, several other studies showed either no association or even found a negative association between HDL-C and FMD [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, ET-1 has been associated with heart failure, hypertension, atherosclerotic vascular, and T2DM. As obesity increases, the induced ET-1 vasoconstrictor tone force increases, whereas the endothelium-dependent vasodilation decreases (20,21). An original study found that culturing arterial endothelial cells and increasing their resistance could generate a significant reduction in endothelial cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Resistin may also accelerate the development of atherosclerosis through its contribution to endothelial dysfunction. Resistin increases the release of endothelin-1 (ET-1), vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), vascular endothelial growth factor receptors (VEGFRs), matrix metalloproteinases (MMPs) and monocyte chemotactic protein-1 (MCP-1), which results in endothelial dysfunction and thus may promote the advancement of atherosclerosis [ 18 , 38 , 39 ]. Moreover, resistin induces pentraxin 3, an inflammatory cytokine involved in atherosclerotic processes in human endothelial cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%